A New and Postmodern Theory of Malaysian Corporatism? Preliminary Conceptual and Theoretical Outline - Khairil Annuar, Mohd Kamal (Faculty of Economics and Business, 2012)
In this paper I outline and discuss the theories and concepts that I am using in my research on Malaysia Inc and Malaysian Corporatism. Malaysia Incorporated can be described to be a product of an authoritarian form of corporatism. This concept started out as a seemingly innocent policy to encourage cooperation between the private sector and government; but has now evolved into a form of corporatism. In this paper I consider some of the theoretical and conceptual discussions. In this paper I will outline the key concepts and theories that will be used as foundations to build my theory of Malaysian Corporatism.